Role of calcium acid phosphate as corrosion inhibitive pigment - Vetere, Vicente Francisco (1994)
Chromate based anticorrosive pigments are gradually being replaced because of their toxicity and carcinogenic properties. Zinc phosphate has been used to replace chromates but has led to contradictory results, its main difficulty being low solubility. Calcium acid phosphate, which has a higher solubility, could replace zinc phosphate. Evaluations of the degree of rusting on painted panels, corrosion rate measurements, and electrochemical studies ( corrosion potential measurements and polarisation curves) have shown that calcium acid phosphate is better than zinc phosphate and is comparable to zinc tetroxychromate as an anticorrosive pigment in a phenolic chlorinated rubber binder. An advantage from an ecological point of view is that calcium ions provide less contamination than zinc ions.